2022
DOI: 10.1371/journal.pone.0274592
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the impact of human capital and supply chain competitive drivers on firm performance in a developing country

Abstract: Purpose This paper aims to determine the effect that human capital and key competitive drivers such as quality, agility, and cost have on firm performance, whether this effect is related to the firm’s outsourcing strategy, and whether the firm size is relevant in explaining such relationships. Design This study uses structural equation modeling to test the hypothesized relationships for small to medium enterprises (SMEs) and large organizations using a custom survey based on a review of the literature and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…Therefore, further investigation is needed to verify this hypothesis and its implications for hiring practices, training and development initiatives in the SCM industry. These findings challenge the study ofSanta et al (2022), which posits that technical skills are the primary requirement in SCM job listings. Our methodology was designed to provide a comprehensive evaluation of SCM competencies beyond technical skills.…”
mentioning
confidence: 56%
“…Therefore, further investigation is needed to verify this hypothesis and its implications for hiring practices, training and development initiatives in the SCM industry. These findings challenge the study ofSanta et al (2022), which posits that technical skills are the primary requirement in SCM job listings. Our methodology was designed to provide a comprehensive evaluation of SCM competencies beyond technical skills.…”
mentioning
confidence: 56%
“…For example, Yao et al (2022) found that enterprise scale reduces the negative impact of financing constraints on firm performance, that is, smaller firms suffer more from restrictions on financing. Santa et al (2022) reported a positive relationship between cost and quality strategies and performance in large organisations but not for SMEs. Firm size, growth and performance are frequently correlated because large companies are more likely to have more resources, which enhances their ability to gather and analyse information and gives the company a competitive edge.…”
Section: Firm Size and Performancementioning
confidence: 94%
“…Businesses using a strategic outsourcing perspective seem to put greater emphasis on boosting flexibility, following cost elements, to the benefit of 3PL service providers' skill to adapt to shifts in demand, while placing a lesser emphasis on enhancing client service and the ability for breakthroughs [22]. Based on the findings of the same study, even though it is mentioned in the research as being one of the essential factors for choosing 3PL services, sustainability was not judged to be extremely relevant.…”
Section: Demand For 3pl Servicesmentioning
confidence: 96%